A discontinuous finite element suspended sediment transport model for water quality assessments in river networks. Issue 9 (9th March 2017) - Fiengo Pérez, Fabricio; Sweeck, Lieve; Elskens, Marc; Bauwens, Willy
Abstract: Suspended sediment plays an important role in the distribution and transport of many pollutants (such as radionuclides) in rivers. Pollutants may adsorb on fine suspended particles (e.g. clay) and spread according to the suspended sediment movement. Hence, the simulation of the suspended sediment mechanism is indispensable for realistic transport modelling. This paper presents and tests a simple mathematical model for predicting the suspended sediment transport in river networks. The model is based on the van Rijn suspended load formula and the advection–diffusion equation with a source or sink term that represents the erosion or deposition fluxes. The transport equation is solved numerically with the discontinuous finite element method. The model evaluation was performed in two steps, first by comparing model simulations with the measured suspended sediment concentrations in the Grote Nete–Molse Nete River in Belgium, and second by a model intercomparison with the sediment transport model NST MIKE 11. The simulations reflect the measurements with a Nash‐Sutcliffe model efficiency of 0.6, while the efficiency between the proposed model and the NST MIKE 11 simulations is 0.96. Both evaluations indicate that the proposed sediment transport model, that is sufficiently simple to be practical, is providing realistic results.